Dressing materials using herbal drugs for better wound management - Biswas A.; Sahu M.; Maiti P. (My University, 2025)
In this chapter, better wound management using different herbal drugs loaded wound dressing materials has been discussed. The wound healing is a complex phenomenon and it passes through mainly three overlapping phases, where cell to cell and cell to matrix interactions take place. Due to complexity of the wounds, different types of dressing materials are required for faster healing. The traditional herbal medicines have a long history of wound management but often their low bioavailability decreases their efficacy. The encapsulation of herbal drug in polymer matrix increases their efficiency for wound healing. Amongst modern dressing materials, hydrogels, polymeric films and scaffolds have the capability to load very high concentration of drug and also have the ability to release them in a controlled and sustained manner which is essential for optimal therapeutic concentration. Further, they have the capability to absorb the exudate, pass the oxygen and also help the cells to be attached and proliferate. In-vivo and clinical studies show better healing efficiency of the herbal drug loaded dressing materials as compared to pure drug or pure dressing materials. © 2018 Nova Science Publishers, Inc.